DETERMINING THE RELATIONSHIPS AMONG INDIVIDUAL VALUES OF EMPLOYEE AND ORGANIZATIONAL CONFLIC MANAGEMENT: A RESEARCH ON PUBLIC ADMINISTRATORS - Alper GÜRER (Fırat University, 2019)
At this study, the relationships among the in